2018
DOI: 10.15171/joddd.2018.030
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different periodontal ligament simulating materials on the incidence of dentinal cracks during root canal preparation

Abstract: Background. The present study was undertaken to evaluate the incidence of dentinal cracks during root canal preparation with different periodontal ligament simulating materials in vitro. Methods. Seventy freshly extracted human mandibular first premolars were selected and divided into 7 groups in terms of simulating material: group 1: polyether impression material; group 2: polyvinyl acetate adhesive; group 3: polyvinyl siloxane impression material; group 4: cyanoacrylate adhesive; group 5: epoxy resin adhesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 20 publications
0
19
0
Order By: Relevance
“…Then, the tooth was embedded in self-polymerized acrylic resin to 2.0 mm below the coronal level. Thereafter, the root was removed from the acrylic block, and the wax was replaced with polyvinyl silicon impression material (Honigum Light, DMG, Hamburg, Germany), which represents the periodontal ligament 21,22…”
Section: Methodsmentioning
confidence: 99%
“…Then, the tooth was embedded in self-polymerized acrylic resin to 2.0 mm below the coronal level. Thereafter, the root was removed from the acrylic block, and the wax was replaced with polyvinyl silicon impression material (Honigum Light, DMG, Hamburg, Germany), which represents the periodontal ligament 21,22…”
Section: Methodsmentioning
confidence: 99%
“…Without simulating such an effect, load test results would be misleadingly high [55]. In the current study, polyvinyl siloxane material was used to simulate the PDL, which was demonstrated to be a good option by Rathi et al [42]. In the current study, acrylic resin with an elastic modulus of around 2000 MPa [56] was used to embed the teeth, resembling the alveolar bone [43,57].…”
Section: Discussionmentioning
confidence: 85%
“…The root portion of the teeth was covered with a thin layer (0.35 mm) of light polyvinyl siloxane material (Virtual extra light body, Ivoclar Vivadent, Schaan, Liechtenstein) to simulate the periodontal ligament [42]. Then, the teeth were embedded in auto-polymerizing acrylic denture base resin (Probase Cold, Ivoclar Vivadent, Schaan, Liechtenstein) at 2 mm apical to the cementoenamel junction (CEJ) to simulate alveolar bone level [43].…”
Section: Methodsmentioning
confidence: 99%
“…To imitate physiological tooth mobility, all roots of the selected teeth which were covered with an artificial periodontal membrane to simulate the movement of a tooth with a healthy periodontium. This layer made a thin layer (0.3mm-0.5mm thickness) of poly vinyl acetate (PVA) (22) , this technique used as it simple and allows to get a uniform thickness of the material all over the entire surface of the root.…”
Section: Discussionmentioning
confidence: 99%